2018
DOI: 10.1080/09540121.2018.1533238
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to preexposure prophylaxis use among individuals with recently acquired HIV infection in Northern California

Abstract: Barriers to HIV preexposure prophylaxis (PrEP) use have not been well-characterized in people who became HIV-infected, all of whom could have benefited from PrEP. We invited members of Kaiser Permanente Northern California with an HIV diagnosis during 2014-2016, following a negative HIV test in the year prior to diagnosis, to complete a survey assessing barriers to PrEP use prior to HIV diagnosis. We used chi-square tests to identify factors associated with specific barriers, and Cochran-Armitage tests to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 33 publications
3
31
2
Order By: Relevance
“…84.1% of participants had heard of PrEP [160] Race/ ethnicity c,d Survey of a Northern California consortium of individuals with recently acquired HIV (N = 122), the majority of whom were MSM (84%) and of minority racial/ethnic background (64%) A lack of PrEP awareness was noted in 69% of Black participants [161] Survey of Black individuals in the USA (N = 855)…”
Section: Years 69%mentioning
confidence: 99%
See 1 more Smart Citation
“…84.1% of participants had heard of PrEP [160] Race/ ethnicity c,d Survey of a Northern California consortium of individuals with recently acquired HIV (N = 122), the majority of whom were MSM (84%) and of minority racial/ethnic background (64%) A lack of PrEP awareness was noted in 69% of Black participants [161] Survey of Black individuals in the USA (N = 855)…”
Section: Years 69%mentioning
confidence: 99%
“…Greater medical mistrust was associated with lower willingness to take PrEP [181] cis cisgender, HIV human immunodeficiency virus, MSM men who have sex with men, PrEP pre-exposure prophylaxis, PWID people who inject drugs, TGW transgender women a Please see study of Black MSM in the ' 'Sexual orientation'' category, also applicable here [188] b Please see study of Black MSM aged 16-25 years in the ' 'Sexual orientation' ' category, also applicable here [189] c Please see study of Black MSM in the ' 'Sexual orientation' ' category, also applicable here [174] Cost/insurance concerns were reported as barriers in 36% of patients [161] Interviews with MSM at Rhode Island Department of Corrections (N = 26)…”
Section: History Of Substance Abusementioning
confidence: 99%
“…Overall, the literature suggests that a key barrier to PrEP uptake is a lack of awareness or insufficient knowledge about PrEP, especially with younger people, black and Latino MSM, transgender people, and individuals with lower education and income levels. [10][11][12][13][14][15][16] Information about PrEP is not reaching all at-risk groups, and there is significant variability in the source and quality of the information. Perez-Figueroa et al found that only half of their study participants (N=100) who were young MSM living in New York City had "some knowledge" about PrEP as a form of HIV prevention.…”
Section: Lack Of Awareness or Insufficient Knowledge About Prepmentioning
confidence: 99%
“…Another barrier is that some persons with HIV risk factors do not feel sufficiently at-risk for HIV to warrant PrEP [5][6][7][8], which relates to perceptions of risk not health systems issues. Studies comparing perceptions of HIV risk against HIV risk scores showed differences in how personal risk-taking was viewed, with many believing their behaviours were "too low-risk" to warrant PrEP [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%